Emerging implications of N6-methyladenosine in prostate cancer progression and treatment - Junyan Xu; Dajun Gao; Changjie Ren; Zhong Wang; Fuwen Yuan; Yanting Shen (Cell Death Discovery)
Abstract RNA modifications are widely distributed in almost all types of RNA, including mRNA, rRNA, miRNA, circRNA, and lncRNA, which are deeply involved in disease initiation and progression and are emerging therapeutic targets in diseases such as cancer, among which N6-methyladenosine (m6A) is the most abundant mRNA modification. Accumulating studies have demonstrated the critical role of m6A during cancer progression and its therapeutic potential in prostate cancer, which is one of the most common malignancies in men worldwide. Here, we reviewed the emerging roles of m6A regulators, including readers, writers, and erasers, and the downstream m6A-modified mRNA and noncoding RNA in prostate cancer. We also discussed the therapeutic potential of targeting m6A in prostate cancer and summarized the emerging agents and technologies, such as the cutting-edge CRISPR-Cas13 in prostate cancer treatment by targeting m6A regulatory pathways. At last, we elucidated the perspective of developing efficient and specific RNA targeting agents and technological platforms to provide new strategies for treating prostate cancer by targeting RNA modifications.